Konsep Kurikulum Alternatif Pendidikan Nonformal di Daerah Terpencil: Kajian Literatur Berbasis Pengembangan Kurikulum Model Taba - Oktin Kristina Hutapea; Budiyono Budiyono (Jurnal Ilmiah Global Education, 2026)
National curriculum policies in Indonesia are designed to ensure educational quality standards; however, their uniform and centralized implementation often overlooks the social, cultural, and geographical contexts of communities, particularly in remote areas. This condition results in formal curricula that are less relevant and do not fully address the learning needs of local communities. Nonformal education has emerged as an alternative space that enables the development of more flexible and contextual curricula. This article aims to critically and descriptively examine the concept of alternative curricula in nonformal education in remote areas through a qualitative literature review, integrating the Taba Curriculum Development Model as an analytical framework. Research data were obtained from key reference books, national and international journal articles, and education policy documents. Data analysis was conducted using qualitative thematic analysis with a descriptive–interpretative and critical approach. The findings indicate that alternative curricula in nonformal education emphasize flexibility, local relevance, community participation, and empowerment-oriented learning. The integration of the Taba Model demonstrates that curriculum development based on local needs can be carried out in a systematic and reflective manner. This study underscores that alternative curricula function not only as a pedagogical solution but also as a theoretical critique of national curriculum policies that have not yet fully ensured educational equity for communities in remote areas.